A multicenter randomized phase III study for newly diagnosed maximally resected glioblastoma comparing carmustine wafer implantation followed by chemoradiotherapy with temozolomide with chemoradiotherapy alone; Japan Clinical Oncology Group Study JCOG1703 (MACS study). (4th December 2019) - Kadota, Tomohiro; Saito, Ryuta; Kumabe, Toshihiro; Mizusawa, Junki; Katayama, Hiroshi; Sumi, Minako; Igaki, Hiroshi; Kinoshita, Manabu; Komori, Takashi; Ichimura, Koichi; Narita, Yoshitaka; Nishikawa, Ryo
Abstract: A randomized phase III trial in Japan commenced in June 2019. The present standard treatment for newly diagnosed glioblastoma is maximal resection followed by chemoradiotherapy with temozolomide. The purpose of this study is to confirm the superiority of maximal resection with carmustine wafer implantation followed by chemoradiotherapy with temozolomide over the standard maximal resection followed by chemoradiotherapy with temozolomide in terms of overall survival for newly diagnosed glioblastoma. A total of 250 patients will be accrued from 35 Japanese institutions in 5.5 years. Patients with >90% surgical resection will be registered and randomly assigned to each group with 1:1 allocation. The primary endpoint is overall survival and the secondary endpoints are progression-free survival, loco-regional progression-free survival and incidence of adverse events. This trial has been registered in the Japan Registry of Clinical Trial, as jRCT1031190035 [https://jrct.niph.go.jp/en-latest-detail/jRCT1031190035 ]. Abstract : A multicenter randomized phase III trial to confirm the superiority of maximal resection with carmustine wafer implantation followed by chemoradiotherapy with temozolomide over standard treatment for newly diagnosed maximal resected glioblastoma.